2016
DOI: 10.3233/jad-150946
|View full text |Cite
|
Sign up to set email alerts
|

Predictors of Mortality in Dementia: The PRIME Study

Abstract: The findings confirm that demographic and diagnostic features predict the survival of patients with dementia. Importantly, the findings indicate that changes in dementia severity and functional impairment over time predict mortality independently of baseline levels, and provide further evidence for the higher mortality risk of patients taking antipsychotic medications.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

18
51
1
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 59 publications
(71 citation statements)
references
References 31 publications
18
51
1
1
Order By: Relevance
“…Although change scores can vary slightly for a number of reasons, including natural fluctuations in participants' performance and different testing conditions, greater levels of decline in these measures are likely to reflect more severe pathophysiology and indicate longer-term trajectories. It is consistent with research in older people, both with and without dementia, that has found that more rapid decline over time predicts a range of future clinical outcomes, such as institutionalisation and mortality [20,21,22,23]. …”
Section: Discussionsupporting
confidence: 62%
See 1 more Smart Citation
“…Although change scores can vary slightly for a number of reasons, including natural fluctuations in participants' performance and different testing conditions, greater levels of decline in these measures are likely to reflect more severe pathophysiology and indicate longer-term trajectories. It is consistent with research in older people, both with and without dementia, that has found that more rapid decline over time predicts a range of future clinical outcomes, such as institutionalisation and mortality [20,21,22,23]. …”
Section: Discussionsupporting
confidence: 62%
“…In particular, we examined whether baseline characteristics, such as cognition and function, predicted driving cessation over the following 3 years. As variables assessing rate of change, such as decline in cognition and function over 6 months, have been shown to predict other clinical outcomes, such as institutionalisation and mortality, in older people [20,21,22,23], we also examined whether these variables predicted subsequent driving status. …”
Section: Introductionmentioning
confidence: 99%
“…Indeed, greater cognitive symptom scores were associated with a greater than 50% reduction in median survival, from 622 days to 282 days. In general, our results comport with other investigations using systematic measures of cognition or measures of frailty or physical functioning and add to the established literature on symptom severity predicting mortality in dementia . While we could not identify a comparable hospital‐based study, a recent Taiwanese claims‐based study predominantly identified comorbidities and overall utilization to be associated with mortality risk in 37,000 patients with dementia .…”
Section: Discussionsupporting
confidence: 75%
“…To evaluate the derived cognitive symptom scores, we examined the extent to which the cognitive score was associated with subsequent dementia risk among hospitalized individuals without a prior diagnosis of dementia. Secondarily, we examined the association between this score and death among hospitalized individuals already diagnosed with dementia, hypothesizing that a common set of features might also represent a marker of disease progression and severity, shown to associate with mortality …”
Section: Introductionmentioning
confidence: 99%
“…In this large community-based old age cohort, greater variability in RT performance but not slower mean RT predicted all-cause mortality while adjusting for conventional mortality risk factors of age, sex, cardiovascular risk and APOE ɛ4 status and important potential confounders of low global cognition and prodromal dementia, both known to be associated with greater IIV RT [4, 35] and increased mortality risk in old age [12, 13, 36]. Following removal of known incident dementia cases, the association between IIV RT and time to death in the multivariable model decreased slightly and failed to reach significance.…”
Section: Discussionmentioning
confidence: 99%